THE COURSE OF PREGNANCY, CHILDBIRTH AND POSTPARTUM PERIOD IN WOMEN WITH UTERINE FIBROIDS - Isakulova M.M; Ibragimova N.S; Boboniyozova X.A (TADQIQOTLAR, 2025)
Abstract. The authors of the work conducted a retrospective analysis aimed at studying the characteristics of the course of pregnancy and childbirth in women at risk for miscarriage with uterine fibroids. Based on the conducted research, the most significant risk factors for the development of uterine fibroids are described, and the frequency of complications during pregnancy and childbirth is identified. Based on the results obtained, general recommendations for the management of pregnancy and childbirth are given.